Assessing larval fish diversity and conservation needs in the Luzon strait using DNA barcoding - Li, Haitao; Chen, Yiyong; Li, Xi; Zhou, Peng; Xiong, Xiaofei (Frontiers in Marine Science, 2023)
Introduction Accurate species identification and biodiversity assessment of larval fish are essential for effective management and conservation of fisheries resources, as it allows for the estimation of parent stocks, assessment of future recruitment, and prediction of spawning and nursing grounds. However, traditional morphology-based identification methods have inherent limitations, highlighting the need for accurate and efficient techniques to address these challenges effectively. The Luzon Strait, a crucial channel connecting the South China Sea to Western Pacific Ocean, is renowned for its fish biodiversity. However, our knowledge of the biodiversity status of larval fish species in this region remains insufficient. Methods Here we employed DNA barcoding to assess larval fish species diversity in the Luzon Strait and adjacent waters. We investigated the species composition, diversity, and geographical distribution of larval fish communities in the region. Moreover, we assessed habitat types, human uses, and IUCN conservation status of each larval fish species. Results A total of 385 larval fish individuals were collected from 15 stations, and 354 individuals were successfully barcoded and identified, representing 147 species from 93 genera, 44 families, and 22 orders. The interspecific Kimura 2-parameter (K2P) divergence exhibited a significant increase of approximately 55-fold higher than intraspecific divergence. The phylogenetic neighbor-joining tree confirmed the distinct lineages for each taxonomic level, demonstrating the feasibility of DNA barcoding. We observed notable variations in fish species diversity and community composition among sampling stations. Non-metric multidimensional scaling analysis revealed greater diversity and dissimilarity of larval fish community compositions in the western regions compared to the eastern regions. This pattern corresponded to the grouping based on the path of the Kuroshio current, suggesting its influence on the fish community structure. Additionally, economically valuable species were identified at these stations, highlighting their ecological significance as potential spawning or nursery grounds for larval fish. We also examined the habitat type, human use, and conservation status of each larval fish species, providing comprehensive insights into their ecological significance and conservation needs. Discussion The establishment of a local DNA sequences database through DNA barcoding will greatly enhance the accuracy of species identification in environmental DNA (eDNA) metabarcoding applications. Altogether, this study offers valuable information for identifying important spawning and nursing grounds of fish populations, thereby supporting sustainable management and conservation of fisheries resources in this region.